Profil Keterampilan Berpikir Kritis Peserta Didik SMP dalam Pembelajaran IPA Materi Sistem Peredaran Darah - Amalia, Noor Fitri; Minarti, Ipah Budi; Budiastuti, Budiastuti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
Critical thinking skills are one of the life skills that are becoming a paradigm in 21st century education. The purpose of this research is to describe the profile of critical thinking skills of junior high school students in the subject of the human circulatory system. The design of this research is descriptive qualitative research. The research subjects were class VIII A of SMP N 6 Semarang, which consisted of 32 students. The research instrument was in the form of documentation of students' answers on student worksheets based on high order thinking skills (HOTS). The results of the answers as research data were analyzed using the indicator rubric of critical thinking skills according to Ennis. The results showed that the average percentage of students who achieved critical thinking skills was 47.5%. In the aspect of giving simple explanations of 25%, building basic skills 75%, concluding 25%, providing further explanations of 50%, and managing strategies and tactics 62.5%. The conclusion of this study is that the profile of students' critical thinking skills as a whole in the circulatory system material is included in the medium category. The implications of this research can provide information regarding the level of students' critical thinking skills in each indicator presented, which will be useful for teachers. as material for reflection and giving feedback to students.